Geographic distribution and phenetic skull variation in two close species of Graomys (Rodentia, Cricetidae, Sigmodontinae) - Martínez, Juan José (2011)
The interspecific differentiation of South American rodents of the genus Graomys was assayed at ecological and morphometric levels in two species. At the ecological level, niche modelling was used. At the morphometric level, the hypothesis that the size and shape of the skull vary with the geographic location was tested using geometric morphometrics by assessing the extent and spatial distribution of phenotypic skull variation within and among two species, Graomys griseoflavus and Graomys chacoensis. Our results of niche modelling indicate the spatial differentiation between the two species, with G. chacoensis inhabiting preferably the Chaco ecoregion and G. griseoflavus inhabiting mainly the Monte ecoregion. In multiple linear regressions, approximately 20% of the skull size variation is explained by latitude, altitude, and temperature seasonality. The partial least square analysis reveals strong correlation between shape and environmental variables, mainly with latitude, annual mean temperature, and annual precipitation. Discrimination between G. griseoflavus and G. chacoensis was highly reliable when using geometric morphometric tools. These results permit us to elucidate some evolutionary processes that have occurred in these species.